The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-294x.2007.03322.x
|View full text |Cite
|
Sign up to set email alerts
|

Egg production and individual genetic diversity in lesser kestrels

Abstract: Fecundity is an important component of individual fitness and has major consequences on population dynamics. Despite this, the influence of individual genetic variability on egg production traits is poorly known. Here, we use two microsatellite-based measures, homozygosity by loci and internal relatedness, to analyse the influence of female genotypic variation at 11 highly variable microsatellite loci on both clutch size and egg volume in a wild population of lesser kestrels (Falco naumanni). Genetic diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 87 publications
2
70
0
Order By: Relevance
“…ongoing climate change (Cobben et al 2012). Furthermore, low genetic variability may also lead to decreased individual fitness (Lacy 1997;Ortego et al 2007). A potential manifestation of the above principle could be the very low female fecundity that we recorded in the present study, although we do not have any direct evidence for its genetic basis.…”
Section: Discussionmentioning
confidence: 52%
“…ongoing climate change (Cobben et al 2012). Furthermore, low genetic variability may also lead to decreased individual fitness (Lacy 1997;Ortego et al 2007). A potential manifestation of the above principle could be the very low female fecundity that we recorded in the present study, although we do not have any direct evidence for its genetic basis.…”
Section: Discussionmentioning
confidence: 52%
“…It is thus surprising that many studies have pooled samples from multiple populations or subpopulations (e.g. Acevedo-Whitehouse et al 2005; Gage et al 2006;Ortego et al 2007;Välimäki et al 2007). Demographic impacts on the strength of HFCs may be obscured in such studies.…”
Section: A Brief Review Of Hypotheses Explaining Heterozygosityfitnesmentioning
confidence: 99%
“…We also found a negative relationship between heterozygosity and egg volume, with weak negative trends for egg mass. While several studies have reported a positive relationship between clutch size and heterozygosity (Foerster et al 2003;Ortego et al 2007;Wetzel et al 2012), few studies have examined the relationship between heterozygosity and other clutch parameters. Indeed, the only other clutch parameter examined was egg size, and some studies found a positive effect of heterozygosity (Forstmeier et al 2012;Wetzel et al 2012) or no effect (Ortego et al 2007) probably because individuals trade-off egg size with clutch size (Smith et al 1989;Nager et al 2000).…”
Section: Heterozygosity Body Size and Reproductionmentioning
confidence: 99%
“…Mojica and Kelly 2010). In studies investigating HFCs, fitness components are often considered separately with, for example, heterozygosity and shortterm survival (Bean et al 2004;Canal et al 2014) or heterozygosity and clutch size (Ortego et al 2007;Wetzel et al 2012). When more complex approaches are undertaken, the traits considered (heterozygosity and morphological traits such as body mass) typically act simultaneously on a single component of fitness such as survival (Richardson et al 2004).…”
Section: Introductionmentioning
confidence: 99%